EFFICACY OF PCSK9 INHIBITORS IN ADDITION TO BACKGROUND STATIN THERAPY COMPARED WITH PLACEBO IN ACHIEVING LDL-C TARGETS IN ADULTS WITH HYPERLIPIDAEMIA: A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - DAS, PRANAB; BORAH, MUKUNDAM (International Journal of Current Pharmaceutical Research, 2026)
Objective: To evaluate the effect of Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9) inhibitors, compared with placebo, when added to background statin therapy, on the proportion of adults with hyperlipidaemia achieving low-density lipoprotein cholesterol (LDL-C)<1.8 mmol/l or ≥50% reduction from baseline. Methods: A systematic search of PubMed, Scopus, Cochrane Library, and Google Scholar (2015–2025) identified randomized controlled trials (RCTs) enrolling adults (≥18 y) with hyperlipidaemia on background statin therapy. Eligible trials compared any PCSK9 inhibitor to placebo, reporting binary outcomes for LDL-C target attainment. Data extraction and risk of bias assessment followed PRISMA 2020 guidelines. Random-effects meta-analysis was performed to calculate pooled risk ratios (RR) with 95% confidence intervals (CI). Heterogeneity (I²), publication bias, and sensitivity analysis were conducted. Results: Five RCTs (n>50,000 participants) were included. PCSK9 inhibitors significantly increased the likelihood of achieving LDL-C targets versus placebo (pooled RR = 2.57, 95% CI: 2.52–2.63). Individual study RRs ranged from 1.89 to 31.37. Heterogeneity was high (I² = 99.86%), largely influenced by one outlier study; removal of this trial reduced I² to 61.39%. All studies had low risk of bias, and no evidence of publication bias was detected. The GRADE certainty of evidence was rated as moderate, downgraded for inconsistency. Conclusion: Adding PCSK9 inhibitors to statin therapy substantially improves LDL-C target attainment in high-risk hyperlipidaemia patients, representing a potent adjunctive strategy when conventional lipid-lowering approaches are insufficient.